PENGARUH VARIASI LATIHAN METODE DRILL TERHADAP JUMP SERVE PADA ATLET PUTRA KLUB BOLA VOLI NUSANTARA DELI SERDANG TAHUN 2021 - Fadhalan Al Azmi Nainggolan; Albadi Sinulingga (Program Studi Pendidikan Jasmani Kesehatan dan Rekreasi, 2021)
This study aims to determine the effect of training variations on the drill method on jump serve in male athletes of the Nusantara Volleyball Club in 2021. The drill method is an exercise that can help improve good movement towards jump serve in volleyball and in practice playing at the repetition time. serve jump movement, which is measured in an assessment of the jump serve movement. This research method is an experiment with a research time of 6 weeks, with training for 3 times a week. The number of samples is by random sampling of 12 athletes. All samples of athletes did the form of training that had been arranged in the training program and did a pre-test before training in the initial week and post-test after the end of training in the last week. Analysis of the hypothesis that is, the effect of variations in drill training methods on jump serve on male athletes of the Nusantara Deli Serdang volleyball club in 2021, obtained t-count 28.32 and t-table 1.796 at a significant level = 0.05 then t-count > t - table. Based on the test criteria, namely HO is rejected and Ha is accepted, this study states that there is a significant effect of variations in training methods on volleyball jumping athletes from the Deli Serdang archipelago in 2021.